A alta do recém-nascido da unidade de terapia intensiva neonatal: implicações para a continuidade do cuidado - Suelen Rosa de Oliveira (2009)
The goal of this study is to analyze the mechanisms used during the newborndischarge in UTIN, taking into account the continuity and comprehensive care. Toreach the proposed purposes, a qualitative methodology was used, guided bytheorical-methodological dialectics. The search scenary was the UTIN of a importantpublic municipal hospital in Belo Horizonte, Minas Gerais. Seven health professionalswere involved in the project who directly helped the newborn in UTIN and 11newborn parents that were hospitalized in the unity during the period of collection ofdata. Data was collected through observation and also through individual interviewswith semi-structured rules. They were analyzed using the Content Analysistechnique. Empirical categories emerged from the analysis: "Obtaining the newborndischarge in UTIN, "Guiding parents through the newborn discharge in UTIN, andImplications for the newborn discharge for the continuity of care. The analysis ofdata made chanllenges and potentials of the everyday work of professionals clear inthe UTIN and also the insertion of two parents in that environment, specially whenobtaining neonates discharge with the aim of meeting the newborn and the parentsneeds. The analysis of data settled that the activities developed in the study scenaryby the team in order to obtain the neonates discharge in UTIN are focused on thebiological aspects, having fragilities when treating newborn and newborn parentspsycosocial aspects. The need of empowering parents involvement in newborn caresituations was proved. The study even enabled the recognition of the situations thatshow the advances of the newborn discharge obtention in the UTIN with the aim ofcontinuing with the care and comprehensive care, emphisizing the team work, theaticulation among sectors and services involved in the newborn care and thedialogical communication. The study enabled the recognition of the newborndischarge in the UTIN for other hospital sectors, for other services or homes; itconstitutes a critical assistance stage when the purpose is to guarantee the continuityand comprehensive care to the newborn. It is emphisized the importance of thedischarge planning, the parents involvement and decisions while taking care and theguidance to parents for the continuity of the newborn care after the UTIN discharge.Finally, the guarantee of the assistance continuity and the comprehensive care wasemphisized in the UTIN neonate discharge obtaining process. It requires thearticulation among professionals and services, emphisizing the network assistanceas a promising strategy to favour the comprehensive and continuity of the newborncare.